Evaluation of the chemical quality of coffee grounds composted by various types of decomposers using a scoring system - Marchel Alfaro Sefanya; Jumar Jumar; Akhmad Rizali; Riza Adrianoor Saputra (TROPICAL WETLAND JOURNAL, 2022)
In recent years, the amount of coffee consumption by the Indonesian people has increased. As a result, there is an increase in coffee waste in the form of coffee grounds so it has the potential to have a negative impact on the environment. Proper management is needed so that coffee grounds are not wasted and pollute the environment. Composting is one way to convert coffee grounds into organic fertilizer. The provision of decomposers is useful for accelerating the composting process of coffee grounds so that it affects the quality of the compost produced. This study aims to determine the chemical quality of coffee grounds compost using different decomposers based on the Indonesian National Standard (SNI) 19-7030-2004. This research was carried out in the Compost House Department of Agroecotechnology and Soil Laboratory Department of Soil Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru for three months, from June to August 2021. This research uses quantitative methods (laboratory analysis) to determine the chemical quality of coffee grounds compost. The treatments were decomposers, d1 = EM4, d2 = M21, d3 = Beka, and d4 = Petro Gladiator. The results showed that the use of EM4, M21, BeKa, and Petro Gladiator decomposers produced organic C, total N, P2O5, K2O, Ca, Mg, and C/N ratio of coffee grounds compost in accordance with SNI 19-7030-2004, but the pH value of coffee grounds compost treated with EM4, M21, BeKa, and Petro Gladiator decomposers did not meet SNI 19-7030-2004.